The truth among narrative in women’s research: examples of two Chinese women autobiographical novels - Xie, Yuting; Yasin, Megat Al Imran; Syed Alsagoff, Syed Agil; Ang, Lay Hoon (International Journal Documentation & Research Institute, 2021)
For the exploration of “truth” in the narrative, mainly based on Steph Lawler’s thoughts, this study adopts two contemporary autobiographical pieces written by Chinese women to analyse. The methods of textual analysis and case study will be combined and utilized in it. To discover the connotation and value of the narrative analysis in women’s research, this article will concentrate on types of truth constructed in the examples as well as rationality and significance in specific texts. Through the analysis of these two examples, it can be found that the narrative analysis has a certain worthy for women’s research. People cannot guarantee the objectivity of these female discourses, in fact, women’s subjective narrative can be regarded as a kind of truth. Through specific regional studies of the women's narratives, this article intends to offer a reference for future women’s studies.